Characteristics of Atmospheric Metalliferous Particles during Large-Scale Fireworks in Korea. (8th July 2015) - Shon, Zang-Ho; Jeong, Ju-Hee; Kim, Yoo-Keun
Abstract : The effect of large-scale firework events on urban background trace metal concentrations was investigated using 24 hr data collected over 3 days at three sites in Busan Metropolitan City, Republic of Korea, during the falls (Oct.) of 2011–2013. The firework events increased local background concentrations of trace metals as follows: K (1.72 times), Sr (2.64 times), As (2.86 times), Pb (2.91 times), and Al (5.44 times). The levels of some metals did not always drop to background level one day after the firework event. The contribution of fireworks to trace metal concentration levels (and emissions) for 2011 event was negligible compared to 2012 and 2013 events due to different meteorological conditions (precipitation). In addition, the impact of firework events on the ambient concentration levels of trace metals was likely to be different depending on their chemical speciation. The impact of firework events in Busan on urban air quality (trace metal) was less intense compared to other similar festivals worldwide. The largest emission of trace metals and elements from firework burning was represented by K (128–164 kg), followed by Pb, Cd, Cu, Mg, Ba, As, Al, Ga, Co, and Na.